"Bitten By Shyness": Menstrual Hygiene Management, Sanitation, and the Quest for Privacy in South Africa. Issue 2 (3rd March 2016) - Scorgie, Fiona; Foster, Jennifer; Stadler, Jonathan; Phiri, Thokozile; Hoppenjans, Laura; Rees, Helen; Muller, Nancy
ABSTRACT: Little is known about how menstruation is managed in low-income settings and whether existing sanitation systems meet women's needs. Using the 'Photovoice' method with 21 women in participatory workshops and in-depth interviews, we collected data on menstrual hygiene management in three sites in Durban, South Africa. All women reported using disposable sanitary pads. Although they were aware that disposable pads were nonbiodegradable, incompatible with waterborne flush systems, and fill up pit latrines, they had little experience with reusable products. Considerable energy was devoted to concealing and containing 'menstrual waste, ' and women expressed concern about inadequate privacy during menstruation. All sites lacked discreet disposal options and reliable water access, while outdoor sanitation facilities were considered unsafe. Findings highlight the need for advocacy to improve safety and privacy of facilities for women in this setting.